Natural Products with Activity against Multidrug-Resistant Tumor Cells - Bernardes de Andrade Carli, Camila [UNESP]; Quilles, Marcela Bassi [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Elsevier, 2013)
Multidrug resistance is the main mechanism by which cancers develop resistance to chemotherapeutic drugs. Consequently, it is also an important factor in the failure of many forms of chemotherapy. This review describes the mechanisms of tumor resistance to drugs and the attempts to discover novel compounds that interact with multidrug-resistant tumor cells. The information presented here will facilitate retrospective of studies and the identification of new drug development candidates with the potential to treat cell populations with multidrug-resistance. © 2013 Elsevier Inc. All rights reserved.
Keywords: Multidrug resistance; Natural products; Tumor cells